Efficacy of bismuth for antibiotic‐resistant Helicobacter pylori strains eradication: A systematic review and meta‐analysis. Issue 6 (25th September 2022) - Han, Zhongxue; Li, Yueyue; Kong, Qingzhou; Liu, Jing; Wang, Juan; Wan, Meng; Lin, Minjuan; Lin, Boshen; Zhang, Wenlin; Ding, Yuming; Wang, Shaotong; Mu, Yijun; et al.
Abstract: Background & Aims: Antibiotic resistance of Helicobacter pylori ( H. pylori ) is increasing worldwide, and bismuth quadruple therapy has been recommended as a first‐line regimen in many areas. This study aimed to investigate whether bismuth would improve the eradication rate (ER) of clarithromycin‐/metronidazole‐/levofloxacin‐resistant H. pylori strains and how much additional efficacy bismuth could achieve. Methods: PubMed, EMBASE, Web of Science, and Cochrane Central databases for randomized controlled trials were systematically searched by two independent reviewers until 15 January 2022. Pooled ERs of clarithromycin‐/metronidazole‐/levofloxacin‐resistant H. pylori strains were compared between bismuth‐containing and non‐bismuth therapies. Pooled risk ratios (RRs) with 95% confidence intervals (CIs) were calculated using a random‐effects model. Results: Eight studies enrolling 340 individuals were included. The RRs of pooled ERs compared between bismuth‐containing and non‐bismuth therapies were 1.83 for clarithromycin‐resistant strains (95% CI 1.16–2.89, pooled ER: 76.9% vs. 36.6%, p = .009, I 2 = 0%), 1.39 for metronidazole‐resistant strains (95% CI 1.09–1.78, pooled ER: 86.8% vs. 60.9%, p = .008, I 2 = 37%), 2.75 for dual clarithromycin/metronidazole‐resistant strains (95% CI 1.01–7.52, pooled ER: 76.9% vs. 18.2%, p = .05, I 2 = 0%), and 1.04 for levofloxacin‐resistant strains (95% CI 0.56–1.93, pooled ER: 63.4% vs. 54.3%, p = .90; I 2 = 60%). Bismuth significantly increased the ERs of clarithromycin‐, metronidazole‐, and dual‐resistant strains by 40%, 26%, and 59%, respectively. Subgroup analysis of treatment duration showed that the significantly higher eradication rate for antibiotic‐resistant strains in bismuth‐containing therapy than non‐bismuth therapy was only observed in 14‐day treatment regimens and not in 7‐day regimens ( p = .02 and .17, respectively). Conclusions: Bismuth was most effective in improving the ERs of dual‐resistant H. pylori strains, followed by clarithromycin‐ and metronidazole‐resistant strains. Prolonged treatment duration might effectively improve the efficacy of bismuth in overcoming antibiotic resistance.